Scratch-Induced Wear Behavior of Multi-Component Ultra-High-Temperature Ceramics - Gia Garino; Ambreen Nisar; Abhijith K. Sukumaran; Arvind Agarwal (Ceramics)
Multi-component ultra-high-temperature ceramics (MC-UHTCs) are promising for high-temperature applications due to exceptional thermo-mechanical properties, yet their wear characteristics remain unexplored. Herein, the wear behavior of binary (Ta, Nb)C, ternary (Ta, Nb, Hf)C, and quaternary (Ta, Nb, Hf, Ti)C UHTCs synthesized via spark plasma sintering (SPS) is investigated. Gradual addition of equimolar UHTC components improves the wear resistance of MC-UHTCs, respectively, by ~29% in ternary UHTCs and ~49% in quaternary UHTCs when compared to binary UHTCs. Similarly, the penetration depth decreased from 115.14 mm in binary UHTCs to 73.48 mm in ternary UHTCs and 44.41 mm in quaternary UHTCs. This has been attributed to the complete solid solutioning, near-full densification and higher hardness (~up to 30%) in quaternary UHTCs. Analysis of the worn-out surface suggests pull-out, radial, and edge micro-cracking and delamination as the dominant wear mechanisms in binary and ternary UHTCs. However, grain deformation and minor delamination are the dominant wear mechanisms in quaternary UHTCs. This study underscores the potential of MC-UHTCs for tribological applications where material experiences removal and inelastic deformation under high mechanical loading.